Learning to be a smart citizen. (4th March 2019) - Manchester, Helen; Cope, Gillian
ABSTRACT: The international Smart Cities and the Learning Cities movements are not often linked. However, there are learning questions at stake here. Smart city agendas are often criticised as being technocratic and instrumental, prioritising market-led solutions to urban issues. Such criticism has led to moves to place the citizen at the centre of these discussions. This raises educational challenges: what theories and forms of learning are required for citizens to play a role in the development of digital, urban futures? This paper adopts ethnographic methods to study the assumptions about learning in a Europe-wide smart city project that included a component of citizen-led development. Our argument provides important messages for smart city planners and developers keen to include citizens in smart city development. It suggests that the current 'banking' models of learning adopted in relation to citizen participation are not fit for purpose and that a new model is needed. This needs to recognise citizen learning as situated in social and material contexts and embedded in unequal relations of power, knowledge and resources. We make the case for smart city initiatives to offer city inhabitants critical, creative learning opportunities that begin to address the inequalities that constitute the contemporary smart city.